Find all School-related info fast with the new School-Specific MBA Forum

It is currently 01 Jul 2015, 05:03

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Events & Promotions

Events & Promotions in June
Open Detailed Calendar

For which of the following functions is g(c-d) = g(c) - g(d)

  Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:
1 KUDOS received
Intern
Intern
avatar
Joined: 25 Dec 2012
Posts: 28
Followers: 0

Kudos [?]: 9 [1] , given: 10

For which of the following functions is g(c-d) = g(c) - g(d) [#permalink] New post 11 Feb 2013, 09:09
1
This post received
KUDOS
1
This post was
BOOKMARKED
00:00
A
B
C
D
E

Difficulty:

  35% (medium)

Question Stats:

70% (02:14) correct 30% (01:12) wrong based on 155 sessions
For which of the following functions is g(c-d) = g(c) - g(d) for all positive numbers c and d?

A g(x) = x^3
B g(x) = x+5
C g(x) = \(\sqrt{3x}\)
D g(x) = 5x
E g(x) 15/x


Sometimes I read a problem 5 times in a row... and I still cannot understand what the question is asking. This was one of those... :x
[Reveal] Spoiler: OA
4 KUDOS received
Manager
Manager
avatar
Joined: 09 Feb 2013
Posts: 121
Followers: 1

Kudos [?]: 406 [4] , given: 17

Re: For which of the following functions is g(c-d) = g(c) - g(d) [#permalink] New post 11 Feb 2013, 09:18
4
This post received
KUDOS
exploringm wrote:
For which of the following functions is g(c-d) = g(c) - g(d) for all positive numbers c and d?
A g(x) = x^3
B g(x) = x+5
C g(x) = \(\sqrt{3x}\)
D g(x) = 5x
E g(x) 15/x

Sometimes I read a problem 5 times in a row... and I still cannot understand what the question is asking. This was one of those... :x


This problem arises because in such type of questions the original function is not given. Instead, we have to find a function which can satisfy the constraint mentioned in the question.
Constraint--> g(c-d) = g(c) - g(d)--->(1), where (c-d), c, d are the values of x.
I am directly putting the value in the answer. You can verify the incorrect option by yourself.

Function as per option D is --->g(x) = 5x
Put the value of x = (c-d), we get --->g(c-d) = 5 (c-d) = 5c - 5d----(LHS)
Put the value of x = c, we get --->g(c) = 5 (c) = 5c ----(RHS)
Put the value of x = d, we get --->g(d) = 5 (d) = 5d----(RHS)

Equate RHS & LHS we get--> 5c - 5d = 5c - 5d
Thus equal.

So the answer is D.

Emma
_________________

Kudos will encourage many others, like me.
Good Questions also deserve few KUDOS.

Manager
Manager
User avatar
Joined: 24 Sep 2012
Posts: 90
Location: United States
Concentration: Entrepreneurship, International Business
GMAT 1: 730 Q50 V39
GPA: 3.2
WE: Education (Education)
Followers: 4

Kudos [?]: 86 [0], given: 3

Re: For which of the following functions is g(c-d) = g(c) - g(d) [#permalink] New post 16 Feb 2013, 12:21
In such questions these are the steps I find useful!!

1) The first step is to check whether you could solve the expression stated in the question( in case the expression is too long) or substitute the expression into the solutions in some manner so as to solve it quickly. If so, this is the quickest way out and usually with a little bit of practice, you can start judging whether this step would work or not before you place your pen on the paper to solve the question.

2) The next method is to find whether the solutions can be substituted into the original expression in some way that is fast and quick. This usually takes some time and hence, mostly does not work. However, if the answer options involve numbers instead of expressions, this might work better.

This method is only for those questions in which the answer options and the questions both contain expressions.

3) You could try substitution of base values to confirm.

.
exploringm wrote:
For which of the following functions is g(c-d) = g(c) - g(d) for all positive numbers c and d?

A g(x) = x^3
B g(x) = x+5
C g(x) = \(\sqrt{3x}\)
D g(x) = 5x
E g(x) 15/x


Sometimes I read a problem 5 times in a row... and I still cannot understand what the question is asking. This was one of those... :x

_________________

Thanks
Kris
Instructor at Aspire4GMAT

Visit us at http://www.aspire4gmat.com

Post your queries
Join our free GMAT course

New blog: How to get that 700+
New blog: Data Sufficiency Tricks


Press Kudos if this helps!

Intern
Intern
avatar
Joined: 20 Apr 2013
Posts: 24
Concentration: Finance, Finance
GMAT Date: 06-03-2013
GPA: 3.3
WE: Accounting (Accounting)
Followers: 0

Kudos [?]: 1 [0], given: 99

Re: For which of the following functions is g(c-d) = g(c) - g(d) [#permalink] New post 30 Apr 2013, 21:54
Why is option C Wrong
\sqrt{3(c-d)} = \sqrt{(3c)}-\sqrt{(3d)}
Senior Manager
Senior Manager
avatar
Joined: 16 Dec 2011
Posts: 453
Followers: 11

Kudos [?]: 165 [0], given: 70

Re: For which of the following functions is g(c-d) = g(c) - g(d) [#permalink] New post 30 Apr 2013, 22:08
Rajkiranmareedu wrote:
Why is option C Wrong
\sqrt{3(c-d)} = \sqrt{(3c)}-\sqrt{(3d)}

Option C says g(x) = \(\sqrt{3x}\)

So, g(c-d) = \(\sqrt{c-d}\)
g(c) = \(\sqrt{c}\)
g(d) = \(\sqrt{d}\)

We cannot say that \(\sqrt{c-d}\) = \(\sqrt{c}\) - \(\sqrt{d}\) for all values of c and d
So we cannot say that g(c-d) = g(c) - g(d) for all values of c and d.

Thus, option c is wrong.
Manager
Manager
avatar
Joined: 03 Mar 2013
Posts: 91
Location: India
Concentration: General Management, Marketing
GPA: 3.49
WE: Web Development (Computer Software)
Followers: 0

Kudos [?]: 7 [0], given: 6

Re: For which of the following functions is g(c-d) = g(c) - g(d) [#permalink] New post 04 Jul 2013, 18:48
exploringm wrote:
For which of the following functions is g(c-d) = g(c) - g(d) for all positive numbers c and d?

A g(x) = x^3
B g(x) = x+5
C g(x) = \(\sqrt{3x}\)
D g(x) = 5x
E g(x) 15/x


Sometimes I read a problem 5 times in a row... and I still cannot understand what the question is asking. This was one of those... :x



put c = 3 and d = 2 or directly substitute c and d

we get option D, :)
GMAT Club Legend
GMAT Club Legend
User avatar
Joined: 09 Sep 2013
Posts: 5338
Followers: 310

Kudos [?]: 60 [0], given: 0

Premium Member
Re: For which of the following functions is g(c-d) = g(c) - g(d) [#permalink] New post 14 Jan 2015, 00:30
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________

GMAT Books | GMAT Club Tests | Best Prices on GMAT Courses | GMAT Mobile App | Math Resources | Verbal Resources

Expert Post
2 KUDOS received
EMPOWERgmat Instructor
User avatar
Status: GMAT Assassin/Co-Founder
Affiliations: EMPOWERgmat
Joined: 19 Dec 2014
Posts: 2660
Location: United States (CA)
GMAT 1: 800 Q51 V49
GRE 1: 340 Q170 V170
Followers: 113

Kudos [?]: 745 [2] , given: 49

Re: For which of the following functions is g(c-d) = g(c) - g(d) [#permalink] New post 14 Jan 2015, 22:50
2
This post received
KUDOS
Expert's post
Hi All,

In these types of "function" questions, you can TEST VALUES (especially really simple ones) to find the correct answer.

Let's TEST...
C = 2
D = 1

The question asks us to find the equation that gives us the same result when...

g(2-1) = g(1) is calculated

and when

g(2) - g(1) is calculated

Answer A: g(X) = X^3
g(1) = 1^3 = 1
g(2) - g(1) = 2^3 - 1^3 = 8 - 1 = 7
1 does NOT = 7

Answer B: g(X) = X+5
g(1) = 1+5 = 6
g(2) - g(1) = (2+5) - (1+5) = 7 - 6 = 1
6 does NOT = 1

Answer C: g(X) = \sqrt{3X}
g(1) = \sqrt{3}
g(2) - g(1) = \sqrt{6} - \sqrt{3} = \sqrt{3}(\sqrt{2} - 1)
\sqrt{3} does NOT = \sqrt{3}(\sqrt{2} - 1)

Answer D: g(X) = 5X
g(1) = 5(1) = 5
g(2) - g(1) = 5(2) - 5(1) = 10 - 5 = 5
5 DOES = 5

Answer E: g(X) = 15/X
g(1) = 15/1 = 15
g(2) - g(1) = 15/2 - 15/1 = -15/2
15 does NOT = -15/2

Final Answer:
[Reveal] Spoiler:
D


GMAT assassins aren't born, they're made,
Rich
_________________

Official Guide 2016 Question Breakdown:
http://gmatclub.com/forum/empowergmat-blog-198415.html#p1527977

Rich Cohen
Rich.C@empowergmat.com
http://www.empowergmat.com

GMAT Club Verified Reviews for EMPOWERgmat & Special Discount

EMPOWERgmat Podcast - A Wild Secret About The GMAT Algorithm


SVP
SVP
User avatar
Status: The Best Or Nothing
Joined: 27 Dec 2012
Posts: 1859
Location: India
Concentration: General Management, Technology
WE: Information Technology (Computer Software)
Followers: 23

Kudos [?]: 960 [0], given: 193

For which of the following functions is g(c-d) = g(c) - g(d) [#permalink] New post 21 Jan 2015, 19:59
A g(x) = x^3

Power of "x" is changed, so IGNORE

B g(x) = x+5

"x" is added by constant, so IGNORE

C g(x) = \sqrt{3x}

Power of "x" is changed, so IGNORE

D g(x) = 5x

"x" is multiplied by constant 5, so required result is true


E g(x) 15/x

\(\frac{15}{x} = 15 * x^{-1}\)

Again power of "x" is changed, so IGNORE

Answer = D
_________________

Kindly press "+1 Kudos" to appreciate :)

For which of the following functions is g(c-d) = g(c) - g(d)   [#permalink] 21 Jan 2015, 19:59
    Similar topics Author Replies Last post
Similar
Topics:
5 Experts publish their posts in the topic Among the following functions, for which one is guerrero25 7 10 Aug 2013, 09:20
For which of the following functions is f(a+b) =f(a)+f(b) girl17 5 23 Feb 2006, 15:18
For which of the following functions f is f(x) = f(x-1) rahulraao 6 11 Oct 2005, 23:45
For which of the following functions is f(x) = f(1-x) for mophead 6 01 Sep 2005, 05:14
Display posts from previous: Sort by

For which of the following functions is g(c-d) = g(c) - g(d)

  Question banks Downloads My Bookmarks Reviews Important topics  


GMAT Club MBA Forum Home| About| Privacy Policy| Terms and Conditions| GMAT Club Rules| Contact| Sitemap

Powered by phpBB © phpBB Group and phpBB SEO

Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.